Nitrogen Doping in VO2 Thin Films on Synthetic Mica Substrates Through Mist Chemical Vapor Deposition: Lowering the Metal–Insulator Transition Temperature Toward Smart Windows - Taisei Kano; Hiroyuki Nishinaka; Yuta Arata; Masahiro Yoshimoto (Advanced Materials Interfaces)
Abstract In this study, nitrogen (N) is doped into VO2 thin films through mist chemical vapor deposition (CVD), and the effect of the doping on metal–insulator transition (MIT) temperatures is investigated. The N‐doped VO2 thin films are grown on an SnO2 buffer layer. The N‐doped VO2 lattice spacing tends to expand as the growth temperature decreased, which indicates that the incorporation of N into the lattice is derived from the Ethylenediamine. Secondary ion mass spectrometry (SIMS) is conducted to investigate the relationship between the decrease in the transition temperature and N concentration. The results reveal that the sample grown at 425 °C contains approximately 2 × 1020 cm−3 of N. Thus, efficient nitrogen doping can be achieved through mist CVD. The temperature‐resistance characteristics of VO2 thin films are measured to investigate their electrical properties and MIT temperatures. The results reveal that for undoped samples, the transition temperature slightly decreases with the decrease in the growth temperature. Furthermore, the sample grown at 425 °C exhibits a considerable change in resistance because of MIT at approximately 29.5 °C. These results prove the potential of using mist CVD N‐doped thin films for smart window applications to address future energy problems.